Regulatory and legal support for the reform of the prosecutor’s office in Ukraine in terms of corporate social responsibility - GulakОlena; Pozniakov, Spartak; Iarmolenko, Iuliia; Parkhomenko, Pavlo; Sukmanovska, Lidiia (Interacción y Perspectiva, 2023)
The purpose of this paper is to analyze the level of effectiveness of the prosecutor’s office reform and to identify problematic aspects through the prism of corporate social responsibility. Such factors as: the analysis of scientific work, the organization of the prosecutor’s office activities at the current stage of development of Ukraine, the study of statistical data, data of sociological studies and the effectiveness of interaction of the law enforcement system, analysis of regulations and legal changes, which regulate the activities of the prosecutor’s office in its retrospective allowed to form several conclusions: 1) The need to reform the prosecutor’s office at the present stage is determined by public demand for the implementation of the rule of law and the protection of human and citizens’ rights and freedoms; the need to fulfill the European integration obligations assumed by Ukraine; getting rid of outdated antidemocratic vestiges; 2) Among the main progressive transformations of the legal support of the activity of the Ukrainian prosecutor’s office, it should be noted: deprivation of general supervisory powers, liquidation of investigative units, a significant limitation of representation in courts; creation of new bodies of prosecutorial self-government.